Vernadsky: life, science, features of thinking - P. P. Fedorov (Тонкие химические технологии)
The article describes the contribution of V.I. Vernadsky to science and the scientific worldview. The features of scientific thinking of V.I. Vernadsky, his natural scientific and philosophical interests and the role of Vernadsky’s ideas in the development of the modern scientific world are discussed.